Nonpharmacological treatment of dyscognition in schizophrenia: effects of aerobic exercise . Issue 3 (30th September 2019) - Maurus, Isabel; Röh, Astrid; Falkai, Peter; Malchow, Berend; Schmitt, Andrea; Hasan, Alkomiet
Abstract : Cognitive symptoms are a core feature of schizophrenia and are related to an unfavorable disease outcome. So far, there are no satisfactory pharmacological approaches to address cognitive symptoms. For some time now, aerobic exercise has been demonstrated in various trials to be a promising candidate for this indication. The aim of this brief qualitative review was to present the most recent meta-analyses regarding the capacity of exercise to improve cognition in schizophrenia patients. Additionally, we give a short overview of the effects in other conditions, like healthy subjects and patients with major depression. We conducted a focused literature search using the PubMed database, concentrating on meta-analyses which are based on a systematic search. The most recent meta-analysis investigating the efficacy of aerobic exercise on cognitive impairments in schizophrenia patients provides evidence that exercise has positive effects on cognitive functioning in this population. However, the effect seems not to be specific; there were positive findings regarding healthy subjects and patients with depressive disorders as well, even if they were less consistent. As most available trials have a small to modest sample size and have no consensus with regard to the intervention regime, nor to the assessment of cognition, the findings are difficult to generalize. In the future, standardized clinical trials focusing on the long-term effects of exercise are needed to evaluate whether the improvements in cognition are sustainable.